The Development of Community Language Learning in Improving Human Resource Excellence at Company - Pamuji, Wirawan; Sutomo; Dahliani, Lili (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Staff Development in gaining Excellence is required for any company to create unity to comprehend quality development in improving their way of thinking for delivering cooperation and coordination. This Development Method demands characters in arguing and making quality or products at company with considering comfort and Hand-in-Hand Character for preceding a purpose of work. That in this case, The Manager will know the attitudes in working than knowing only producing good quality product and service as they are commonly understood for manager to comprehend business as well